2014
DOI: 10.1063/1.4896473
|View full text |Cite
|
Sign up to set email alerts
|

Integrated-fin gasket for palm cubic-anvil high pressure apparatus

Abstract: We described an integrated-fin gasket technique for the palm cubic-anvil apparatus specialized for the high-pressure and low-temperature measurements. By using such a gasket made from the semi-sintered MgO ceramics and the tungsten-carbide anvils of 2.5 mm square top, we successfully generate pressures over 16 GPa at both room and cryogenic temperatures down to 0.5 K. We observed a pressure self-increment for this specific configuration and further characterized the thermally induced pressure variation by moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 14 publications
3
51
0
Order By: Relevance
“…For the constant-force apparatus, the pressure was calibrated at room temperature by monitoring the characteristic resistance change of Bismuth (Bi) at 2.55 and 7.7 GPa; 23 for the "Palm" cubicanvil cell, the pressure after clamping was calibrated at low temperatures by monitoring the superconducting transition temperature of lead (Pb). 25 Our first-principles calculations were performed using the all-electron planewave density functional theory code WIEN2K, 26 in an attempt to understand the superconducting state and the potential relevance of magnetism.…”
Section: Methodsmentioning
confidence: 99%
“…For the constant-force apparatus, the pressure was calibrated at room temperature by monitoring the characteristic resistance change of Bismuth (Bi) at 2.55 and 7.7 GPa; 23 for the "Palm" cubicanvil cell, the pressure after clamping was calibrated at low temperatures by monitoring the superconducting transition temperature of lead (Pb). 25 Our first-principles calculations were performed using the all-electron planewave density functional theory code WIEN2K, 26 in an attempt to understand the superconducting state and the potential relevance of magnetism.…”
Section: Methodsmentioning
confidence: 99%
“…However, the pressure and temperature ranges in the previous studies were far from the magnetic QCP. By utilizing the recently developed highpressure techniques [19][20][21][22][23], we have reinvestigated this problem in an extended pressure and temperature range, and surprisingly found that MnP becomes superconducting below T sc ≈ 1 K near the magnetic QCP at P c ≈ 8 GPa. Since the majority of the density of states near the Fermi level for MnP is attributed to the Mn-3d states [24,25], the present discovery makes MnP the first Mn-based superconductor, and the close proximity of SC to a magnetic instability suggests an unconventional pairing mechanism.…”
mentioning
confidence: 98%
“…Using this newly developed PCAC, crystal with several times larger than previously used can be measured under highly hydrostatic condition. [17][18][19] The sample is immersed in the liquid PTM (fluorinert) contained in a teflon capsule.…”
Section: Knownmentioning
confidence: 99%